IMPLEMENTASI ALGORITMA SHA UNTUK ENKRIPSI TEKS BERBASIS MOBILE - Ananda Perdana; Dermawan Rizky Syahputra; Samuel Fernando Manurung; Taufiqul Hafizh; Dedek Hendra Gunawan Hutasuhut (Pusat Riset dan Inovasi Nasional, 2023)
In today's digital era, text messages have become one of the most common communication methods used by many people around the world. However, the use of text messages also poses security risks that need to be considered. Text messages can be targeted by hackers who are after personal information or important data that is sent through text messages. Mobile devices that are always connected to the internet can make text messages easily hacked or intercepted by unauthorized parties. Therefore, the use of encryption methods on text messages is very important to enhance the security and privacy of the information sent through text messages. This research aims to implement the Secure Hash Algorithm (SHA) algorithm on a mobile application for text encryption. The implementation of the SHA algorithm on the mobile application is done using the Java programming language and utilizing Android's built-in library to process data. The results of the study show that the mobile application using the implementation of the SHA algorithm can provide higher security for data containing messages sent over public networks